Chronic Illnesses and Depression among Community-based Adolescents in Rural Haryana, India - Aditi Mohta; Sumit Malhotra; Mani Kalaivani; Bichitra Nanda Patra; Baridalyne Nongkynrih (Indian Journal of Public Health)
Evidence on the association of chronic illnesses with depression among adolescents in the Indian community setting is limited. A simple random sample of 583 adolescents, comprising 56.6% of boys and 43.4% of girls, were interviewed on home visits. Self-reports on chronic illnesses were elicited, followed by administration of Patient Health Questionnaire-9 (PHQ-9) questionnaire to screen for depression, and for confirmation of diagnosis by age-appropriate Mini-International Neuropsychiatric Interview for Children and Adolescents (MINI Kid), or MINI. The prevalence of chronic illnesses was 8.4% (95% confidence interval [CI]: 6.3–11.0). Of these participants, 42.8% screened positive for depression. The prevalence of depression was 10.2% (95% CI: 3.4–22.2) among adolescents with chronic illness. The prevalence of physical–mental multimorbidity was 0.8% (95% CI: 0.3–2.0). The presence of chronic illness was associated with depression identified using both PHQ-9 (adjusted odds ratio [AOR] =3.1 [95% CI: 1.7–5.8], P < 0.001) and MINI Kid/MINI (AOR = 3.2 [95% CI: 1.1–9.4], P = 0.037). Adolescents with chronic illnesses can be targeted for mental morbidity screening in a bid to improve functional outcomes.